EFEKTIVITAS EVALUASI DIRI PROGRAM STUDI (Studi Kasus Analisis SWOT dan Perencanaan Strategis) - Silmi Amrullah (Jurnal Administrasi Pendidikan, 2021)
This study focuses on the effectiveness of self-evaluation of study programs with the SWOT analysis approach. This study is a qualitative descriptive with a case study approach in the S1 accounting program at Parahyangan Catholic University. The results of the study show that first, self-evaluation is carried out by all relevant elements in the study program, to thoroughly determine the performance of the study program seen from the achievement of SPM and SNP. Second, The purpose of self-evaluation is to find out: (1) strengths, (2) weaknesses, (4) opportunities and (4) threats. Third, Supporting Factors include; (1) Human resources, (2) Understanding concepts, (3) Implemen-tation mechanisms (4) sustainable implementation. This research is motivated by the phenomenon of cultural development in universities; therefore, awareness of quality must be improved. Inhibiting factors are felt to be very minimal, obstacles faced such as the existence of conflicts between members. Recommendation; increased supervision by the head of the study program in implementing self-evaluation and involving peer experts from outside the study program so that self- evaluation can be carried out objectively.